Bienestar Animal Y Caracterización De 4 Fincas De Producción Caprina Tecnificadas Y No Tecnificadas En El Departamento De Cundinamarca (2024)
In Colombia, goat farming is a very important factor for the communities of some departments. This is because they are the primary support of its economy and food, including both cultural and social aspects. These communities take benefit of the entire animal, mainly in the production of milk and its derivatives, as well as also in meat production, even in many communities they use the hair for make clothes, rugs, among other crafts. However, goat production in the country is not strongly developed, so it has been shown that this practice is in boom. According to the Colombian Agricultural Institute (ICA), in 2022 there were around 1,149,054 animals, which are mostly found in the departments of La Guajira, Boyacá, Cesar, Magdalena, Santander, Cundinamarca, among others. Therefore, the systems Goat production is not as common compared to cattle production.